Concurrent strongyloidiasis and allergic bronchopulmonary aspergillosis complicating diagnosis: case report - Lin, Zhuangheng; Su, Weiming; Wu, Dinghui; Lin, Yangkun; Jian, Lijuan; He, Zigang; Jiang, Dandan (Frontiers in Medicine, 2025)
Herein, we report a case of allergic bronchopulmonary aspergillosis (ABPA) complicated by Strongyloides stercoralis infection. A 73-year-old man with a history of duodenal ulcer perforation and prior Billroth II gastrectomy presented with a 14-year history of recurrent cough and wheezing, recently accompanied by new gastrointestinal symptoms. He was initially diagnosed with chronic obstructive pulmonary disease (COPD). Subsequent laboratory evaluation revealed a markedly elevated total serum IgE (1,219 kUA/L) and increased Aspergillus fumigatus-specific IgE (0.38 kUA/L, positive cutoff >0.35 kUA/L), leading to a diagnosis of ABPA. Despite antifungal and corticosteroid therapy, total IgE levels remained persistently elevated, accompanied by worsening gastrointestinal symptoms. Multiple stool examinations failed to detect parasitic infection. As gastrointestinal symptoms progressed, gastroscopy revealed the presence of parasitic eggs and larvae. Subsequently, a stool specimen was sent to the Xiamen Center for Disease Control and Prevention. Using the formol-ether concentration technique, the microscopic examination ultimately confirmed an infection with Strongyloides stercoralis. Following albendazole treatment, the patient’s symptoms completely resolved. In conclusion, co-infection of ABPA with Strongyloides stercoralis may lead to missed or delayed diagnosis due to persistently elevated IgE levels.